Improvement of purification process of stevia extract by combination of microfiltration and ultrafiltration - Michael Silaen; Erliza Noor; Mulyorini Rahayuningsih (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2023)
Microfiltration and ultrafiltration are used for the purification process of stevia extract to retain steviosides and remove tannins. The main objective of this study was to obtain the operating conditions for the purification process of stevia extract that resulted in the lowest stevioside rejection and highest tannin rejection. The purification process of stevia extract using microfiltration membrane was carried out at transmembrane pressure (1.20, 1.40, 1.65, 1.80, and 1.90 bar), cross flow velocity (0.04, 0.06, and 0.11 m s-1), and stevioside concentration of feed (7.12, 10.25, 14.03, and 18.47 g L-1). The stevia extract purification process used ultrafiltration membrane at transmembrane pressure (1.20, 1.40, 1.65, 1.80, and 1.90 bar), cross flow velocity (0.06, 0.09, and 0.12 m s-1), and stevioside concentration of feed (4.59 and 10.36 g L-1). The first step purification process was carried out using a microfiltration membrane and the resulting permeate was used as feed for the ultrafiltration process. The second step purification process was carried out using an ultrafiltration membrane. The best operating conditions of the microfiltration process were feed stevioside concentration of 14.03 g L-1 at a transmembrane pressure of 1.90 bar and a cross flow velocity of 0.11 m s-1 with a permeate flux of 82.90 L m-2 h-1. The best operating conditions of the ultrafiltration process used a feed stevioside concentration of 10.36 g L-1 with a permeate flux of 26.51 L m-2 h-1 at a transmembrane pressure of 1.90 bar and a cross flow velocity of 0.12 m s-1. The microfiltration and ultrafiltration processes resulted in total stevioside rejection of 59.52 % and total tannin rejection of 57.99 %.